A novel secretion and online-cleavage strategy for production of cecropin A in Escherichia coli - Meng Wang (Nature Portfolio, 2017)
Abstract Antimicrobial peptides, promising antibiotic candidates, are attracting increasing research attention. Current methods for production of antimicrobial peptides are chemical synthesis, intracellular fusion expression, or direct separation and purification from natural sources. However, all these methods are costly, operation-complicated and low efficiency. Here, we report a new strategy for extracellular secretion and online-cleavage of antimicrobial peptides on the surface of Escherichia coli, which is cost-effective, simple and does not require complex procedures like cell disruption and protein purification. Analysis by transmission electron microscopy and semi-denaturing detergent agarose gel electrophoresis indicated that fusion proteins contain cecropin A peptides can successfully be secreted and form extracellular amyloid aggregates at the surface of Escherichia coli on the basis of E. coli curli secretion system and amyloid characteristics of sup35NM. These amyloid aggregates can be easily collected by simple centrifugation and high-purity cecropin A peptide with the same antimicrobial activity as commercial peptide by chemical synthesis was released by efficient self-cleavage of Mxe GyrA intein. Here, we established a novel expression strategy for the production of antimicrobial peptides, which dramatically reduces the cost and simplifies purification procedures and gives new insights into producing antimicrobial and other commercially-viable peptides.